Cyber Security Policies for Digital India: Challenges and Opportunities - Anurag, Singh Anurag; Brijmohan, Singh (International Journal of Computer Sciences and Engineering, 2025)
India is perched on the cusp of computerized development. The administration has defeated its depreciators with a hawk looked at center to accomplish this objective for the nation. It is currently up to organizations to guarantee they are prepared and arranged to load and attempt the open doors this advancement will bring. The Indian government has lodged on a program to transform the nation into an advanced economy. It has make open a progression of activities—from presenting Digital Locker, which takes out the requirement for individuals to convey printed versions of reports issued by the administration, to demonetization, which has impelled the utilization of computerized installments the nation over. The move towards an advanced economy is probably going to help enact a new rush of financial development, draw in greater venture, and make new employments, over numerous divisions. Notwithstanding, it additionally represents a major test, that of cybersecurity. With the move towards a computerized economy, expanding measure of buyer and national information will be put away carefully and an extensive number of exchanges will be done on the web, by organizations, people and also government divisions. In any case, it additionally represents a major test, that of cybersecurity. With the move towards a computerized economy, expanding measure of shopper and national information will be put away carefully and a substantial number of exchanges will be completed on the web, by organizations, people and also government divisions. That makes India a greater focus for digital lawbreakers and programmers. Different partners, particularly Indian organizations, should be better arranged to deal with this risk. National cybersecurity technique is a fundamental component as cybersecurity is expected to ensure also, empower computerized economy.